Biofortification of Common Bean for Higher Iron Concentration - Beebe, Stephen (Frontiers in Sustainable Food Systems, 2020)
Common bean (Phaseolus vulgaris L.) is a staple food of smallholder farmers and poor urban consumers in Latin America and eastern-southern Africa among whom iron deficiency is frequent. Bean was domesticated in Mexico and the southern Andes, creating two distinct gene pools. Evaluation of a core collection of 1441 entries revealed average concentrations of 55 mg kg-1 iron. A breeding target was set at 44 mg kg-1 iron above the level in a local check variety, while 50% of goal or a 22 mg kg-1 advantage was accepted as “biofortified”. In a bioefficacy trial among college-age women in Rwanda, high iron beans improved iron status and enhanced cognitive ability, brain function, and work efficiency. However, breeding progress has been slow, likely due in part to homeostatic mechanisms whereby organisms moderate iron and zinc uptake. This phenomenon may represent resistance to increasing concentration of these elements. Crosses between gene pools may “jumble” genes for homeostasis and permit high levels. A second breeding strategy is the use of sister species that evolved in iron-poor environments and that could be more receptive to iron uptake. Future breeding may also increase attention on improving bioavailability through mechanisms such as non-or-slow darkening grain or low phytate mutants. Changing dietary patterns in developed countries could increase iron deficiency and create demand for iron biofortified beans.